Bezdomne kobiety w opinii bezdomnych kobiet - Szluz, Beata (TNFS, 2011)
This article was written based on a larger, their own studies that were conducted in 2009 among the 52 homeless women in podkarpackie voivodship. People were matched in terms of age, place of residence during the research and occasional or permanent residence in the hostel. Using autobiographical narrative interview, which is a particular form of free or deep interview. The text attempts to show the opinion of homeless women on their own. It shows the reasons for homelessness women in their opinions and their own characteristics.
HOMELESS WOMEN IN THE OPINION OF HOMELESS WOMEN
-
Keywords: sociology; family; homelessness; family homelessness